2009
DOI: 10.2737/rmrs-gtr-222
|View full text |Cite
|
Sign up to set email alerts
|

Nevada Photo-Based Inventory Pilot (NPIP) photo sampling procedures

Abstract: The Forest Inventory and Analysis program (FIA) of the U.S. Forest Service monitors status and trends in forested ecoregions nationwide. The complex nature of this broad-scale, strategic-level inventory demands constant evolution and evaluation of methods to get the best information possible while continuously increasing efficiency. In 2004, the "Nevada Photo-Based Inventory Pilot" (NPIP) was launched and involved the acquisition and processing of large-scale aerial photography (LSP) throughout the State of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Aspen is present, either as the dominant tree species (1.6 million ac, or 0.6 million ha) or as a subdominant (1.2 million ac, 0.5 million ha) on just over half (55 percent) of the forested lands in the State. The abundance of aspen is similar or less in other Intermountain States (Frescino et al 2016;Witt et al 2012). (15 percent), and State and other agencies (12 percent) (Werstak et al 2016).…”
Section: Scope and Purposementioning
confidence: 99%
“…Aspen is present, either as the dominant tree species (1.6 million ac, or 0.6 million ha) or as a subdominant (1.2 million ac, 0.5 million ha) on just over half (55 percent) of the forested lands in the State. The abundance of aspen is similar or less in other Intermountain States (Frescino et al 2016;Witt et al 2012). (15 percent), and State and other agencies (12 percent) (Werstak et al 2016).…”
Section: Scope and Purposementioning
confidence: 99%
“…The study area covers the Triple Divide region of three major river basins of the western US, including the Colorado, Columbia, and Missouri Rivers, and was determined by calculating a minimum bounding rectangle around the chronosequence of the forest fire perimeters. Forest fire perimeters were defined using the Monitoring Trends in Burn Severity (MTBS) burn perimeters data (Finco et al, 2012) plus a 2 km buffer determined within ArcGIS (Figure 1). The study domain has an average elevation of 2503m (sd = 320m) with a minimum and maximum elevation of 1727m and 3596m respectively (Danielson & Gesch, 2010).…”
Section: Study Regionmentioning
confidence: 99%
“…In a double sampling for post-stratification context, Westfall et al [178] demonstrated the value of PI of WMS-based NAIP imagery for improving inventory efficiency in three counties of Pennsylvania. Frescino et al [179] used digital photographs to conduct an inventory of TOF in Nevada. Lister et al [180] used a rapid PI approach to monitor land use change in Maryland, and Lister et al [181] used a similar method to characterize forest degradation in Maryland and Pennsylvania.…”
Section: Cloud-based Data Hosting and Servingmentioning
confidence: 99%